Pengembangan Computer Based Test (CBT) Ujian Nasional Kimia berbasis Web untuk Siswa Madrasah Aliyah (MA) - Agus Kamaludin (Postgraduate, University of Mataram, 2023)
Computer Based Test (CBT) website-based chemistry national exam is an online-based chemistry exam system in terms of test prep and practice for a national exam, provided with item analysis. The results of the item analysis serve to determine the indicators of questions that are considered difficult by students so that the deepening of the materials is more accurate to the students’ needs. This research aims to develop a computer-based test (CBT) for students of Islamic High School (MA). The product is also categorized as Computer Based Test (CBT) because a computer is required to implement the exam. The development of CBT used the Borg and Gall model with five stages: (1) research and information collecting, (2) planning, (3) developing preliminary products (4) preliminary field testing, and (5) primary product revision. The instruments used were product validation sheets under the authority of media and IT experts, quality assessment sheets from reviewers (chemistry teacher of MA), and student response sheets. Based on the assessment of reviewers (chemistry teachers of MA), the developed product, website-based chemistry test obtained an ideal percentage of 91% with the very good category (VG), and student response was 92% with the very good category (VG). Therefore, it can be concluded that the website-based chemistry test is feasible for national exam practice.